Impacts of converter station faults on the performance of WECS - Alharbi, Y.; Abu-Siada, Ahmed (2015)
The number of doubly fed induction generators (DFIG) connected to the existing network has increased significantly worldwide during the last two decades. The stator in DFIG is directly connected to the grid whereas the rotor is interfaced to the grid through two voltage source converters; rotor side converter (RSC) and grid side converter (GSC), which are considered as the crux of the DFIG system. The converter stations determine the ability of wind turbine to operate optimally during wind speed fluctuation and it can provide reactive power support to the grid during grid disturbance events. This paper investigates the impact of fire-Through and misfire faults in the converter station on the dynamic performance of the DFIG. Detailed simulation is carried out using MATLAB/SIMULINK software.